1966
DOI: 10.1098/rspa.1966.0223
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations of the transition to detonation in an explosive gas

Abstract: The experimental study of transition to detonation has been enhanced recently by two novel techniques. One exploits simply the fact that a self-sustained detonation front, unlike any other wave associated with the transition process, is capable of leaving imprints on the wall along which it travels. The other is based on the adaptation of an amplitude modulated, giant pulse, laser system as a light source for stroboscopic schlieren photography. The insight gained by the utilization of these techniques into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(43 citation statements)
references
References 15 publications
1
41
1
Order By: Relevance
“…High shear rates can be generated in viscous sub-layers [23], which might initiate autoignition of the reactants [26,27], in this case located between the two fronts. In their studies of the autoignitive 'explosion in the explosion', Urtiew & Oppenheim [25] found that it was usually initiated at the boundary layer of the duct wall and was variously aided by weak reflected transverse waves originating from initiating hot spots, the turbulent flame, the main shock front and coalescing shock waves. After such explosions, reaction fronts swept through the unburned mixture, penetrating the leading shock and generating a self-sustained detonation there, often creating triple-wave interactions.…”
Section: Flame Propagation Along a Duct And The Transition To Detonationmentioning
confidence: 99%
See 2 more Smart Citations
“…High shear rates can be generated in viscous sub-layers [23], which might initiate autoignition of the reactants [26,27], in this case located between the two fronts. In their studies of the autoignitive 'explosion in the explosion', Urtiew & Oppenheim [25] found that it was usually initiated at the boundary layer of the duct wall and was variously aided by weak reflected transverse waves originating from initiating hot spots, the turbulent flame, the main shock front and coalescing shock waves. After such explosions, reaction fronts swept through the unburned mixture, penetrating the leading shock and generating a self-sustained detonation there, often creating triple-wave interactions.…”
Section: Flame Propagation Along a Duct And The Transition To Detonationmentioning
confidence: 99%
“…The seminal studies of Urtiew & Oppenheim [25] traced the progress of the flame and planar shock fronts along a duct of rectangular cross section (25.4 × 38.1 mm) closed at one end. These provide further quantitative insights and we shall concentrate in some detail on their equimolar mixtures of H 2 and O 2 , which were less reactive than the stoichiometric mixtures of Meyer & Oppenheim [10].…”
Section: Flame Propagation Along a Duct And The Transition To Detonationmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of detonation following shock formation was reported in other publications by Laderman & Oppenheim [32] and Urtiew & Oppenheim [26], the former of which considered the effects of longitudinal gas-dynamic wave interactions.…”
Section: (I) Flame Acceleration In a Duct Or Pipementioning
confidence: 84%
“…Even for unconfined spherical detonations, transition can often be identified with a small perturbation arising from the support for the flame ignition source or a weak transverse perturbation owing to wave interactions, as in the critical diffraction of a detonation into an unconfined volume. Smirnov & Tyurnikov [23] and Smirnov & Oaniflov [24] have observed several variants of the conditions that lead to the onset of the DDT process, including emergence of detonation from a flame brush, as in the case of Urtiew & Oppenheim [25,26] and Meyer et al [27], as well as transitions owing to the shock-wave merging reported by Urtiew & Oppenheim [28]. (b) Indirect initiation…”
Section: (A) Direct Initiation By a High-energy Sourcementioning
confidence: 99%